Shifty talk: knowledge and causation - Brown, Jessica (Philosophical studies, 2014)
In this paper, I criticise one main strategy for supporting anti-intellectualism, the view that whether a subject knows may depend on the stakes. This strategy appeals to difficulties with developing contextualist and pragmatic treatments of the shiftiness of our talk about knowledge to motivate anti-intellectualism. I criticise this strategy by drawing an analogy between debates about causation and knowledge. In each case, talk about a phenomenon is shifty and contextualist and pragmatic explanations of the shifty talk face the same objections. However, in the case of causation it would be implausible to argue that difficulties with the relevant contextualist and pragmatic accounts motivate a revisionary metaphysics of causation. I conclude that the defender of anti-intellectualism needs to employ a different strategy to defend her view.